On the Conservation of Distance in International Trade - Berthelon, Matias; Freund, Caroline (2012)
Using disaggregated bilateral trade data, we find that the elasticity of trade to distance increased (in absolute value) by about 10% since 1985. To explore the reasons for this shift, we decompose the change in the distance elasticity of trade into the part due to a shift in the composition of trade among industries and the part due to a change in the distance sensitivity within industries. We find that adjustment in the composition of trade had little effect, but for 40% of industries distance became more important, with nearly all of the remaining industries showing no significant change. We explore alternative hypotheses as to why the elasticity of trade to distance increased in some industries. We find that homogeneous goods, bulky goods, and high tariff goods became significantly more distance sensitive. In contrast, the evidence implies that changes in tariffs and freight costs have reduced the importance of distance on trade. We conclude that the increase in the importance of distance over time is related to the substitutability of goods and the level of trade costs, but not to changes in tariffs or freight costs.